Citrate‐assisted efficient local delivery of naked oligonucleotide into live mouse brain cells. (7th May 2019) - Zhou, Haibin; Zhang, Shouhua; Lv, Fei; Sun, Wenzhi; Wang, Lihua; Fan, Chunhai; Li, Jiang; Hu, Ji
Abstract: Objectives: Synthetic oligonucleotides have shown promise in brain imaging. However, delivery of oligonucleotides into live brain cells remains challenging. In this study, we aim to develop a facile yet efficient strategy for local delivery of oligodeoxynucleotide (ODN) to neural cells in live adult mouse brain. Materials and methods: A fluorescence‐labelled ODN was diluted with sodium citrate buffer (100 mmol/L, pH = 3). One microlitre of the mixture was injected into a live adult mouse brain. Six hours later, we sacrificed the mouse and prepared brain slices for microscopic imaging. Results: We find that the use of sodium citrate buffer in the one‐shot local delivery can improve the diffusion and cell entry efficiency of the unmodified ODN for dozens of times. Only 1 pmol ODN leads to hundreds of positively transferred brain cells. We reason that this promotion is due to the local acidic condition created by the citrate buffer, which leads to the protonation of the ODN and some membrane proteins, thus reduces the Coulomb repulsion between the ODN and the cell membrane. Based on this strategy, we demonstrate fluorescent microscopic imaging of brain cells in different brain regions including striatum, cortex, hippocampus and midbrain. Conclusions: The citrate buffer can be used as an adjuvant for facile and effective local injection delivery of ODNs, which may provide a new tool for brain imaging.